Patient Satisfaction on the Utilization of Health Service in Bhaktapur Hospital, Nepal - Bishnu Bahadur Khatri; Tirtha Raj Timsina; Parbata Devi Karki (Journal of Development and Administrative Studies, 2024)
Patient satisfaction is a critical indicator of healthcare quality, reflecting the extent to which services meet patients' expectations. This study aimed to evaluate patient satisfaction with health services at Bhaktapur Hospital, Nepal, to inform quality improvement initiatives and healthcare policy development. Using a cross-sectional design, data were collected from 120 in patients who met inclusion criteria through structured interviews. The study utilized a validated questionnaire, translated into Nepali and English, and analyzed the data using IBM SPSS version 20. Findings reveal high levels of satisfaction with safety, cleanliness, and interpersonal skills of staff, particularly in communication and treatment explanation, with a mean satisfaction score of 3.836 ± 0.468. Accessibility to emergency services, admission processes, and laboratory facilities also received favorable ratings (mean score 3.837 ± 0.439). However, dissatisfaction was noted in toilet services, drinking water facilities, and room service (mean score 3.4476 ± 0.587). Additionally, challenges in specialist availability and pharmacy services were highlighted. Socio-demographic factors such as educational and marital status significantly influenced satisfaction, with graduates and unmarried patients reporting higher dissatisfaction. These findings underscore the need for targeted interventions to address hygiene, basic amenities, and service delivery inconsistencies, particularly in room services and pharmacy access. Enhancing doctors’ attentiveness and respect in patient interactions could further improve interpersonal satisfaction. Addressing these areas is critical for achieving a balanced, high-quality patient experience and advancing healthcare delivery at Bhaktapur Hospital, Nepal.